SYNTHESIS AND CHARACTERIZATION OF THIOLATED JACKFRUIT SEED STARCH AS A COLONIC DRUG DELIVERY CARRIER - Das, Sanjoy; Das, Malay K. (International Journal of Applied Pharmaceutics, 2019)
Objective: Site-specific drug delivery into the colonic region is extremely fascinating for local treatment of various colonic diseases like ulcerative colitis, colon cancer but it should be capable of saving the drug from hydrolysis and degradation. The present study reports the application of jackfruit seed starch and its thiol derivative as a drug delivery carrier for the colon. Methods: The starch was extracted from the jackfruit seeds by water extraction method and modified by the esterification reaction with thioglycolic acid. The thiolated starch was characterized for morphology, functional and flow properties. The safety profile of the thiolated starch was confirmed by acute toxicity study in a mice model as per OECD guidelines 423. The microspheres based on thiolated starch were prepared by ionic gelation method incorporating Ibuprofen as a model drug. The prepared microspheres were characterized for particle size, drug entrapment efficiency, drug loading, compatibility study, surface morphology, in vitro drug release and release kinetics. Results: The result attributed that starch was successfully modified by the thiolation with a degree of substitution of 3.30. The size of prepared microspheres ranges from 825.5±4.58 to 857±6.24 µm, the entrapment efficiencies ranges from 69.23±1.19 to 76.15±0.83 % and the drug loading capacity ranges from 17.75±0.30 to 46.05±0.49 %. The FT-IR, DSC and XRD studies confirmed that there is no interaction within drug and excipients. The thiolated starch microspheres show the maximum release of drug at pH 7.4 in the presence of rat caecal content as compared to pH 1.2 and pH 6.8 for up to 24 h and are following first order release kinetics. Conclusion: These results suggest the application of thiolated jackfruit seed starch could be promising as a long-term drug delivery carrier for the colon.